Сriteria and Indicators of Effectiveness of Management of Practical Preparation of Students in Higher Pedagogical Educational Establishment - Kashchuk, Anna (Pedagogical Discourse, 2012)
The question of valuation of effectiveness of the process of management of practical preparation of the future primary school teachers by means of determination of its main criteria and indicators has been revealed in the article.